2020
DOI: 10.1002/clc.23425
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between cardiac troponin I and nonsustained ventricular tachycardia in hypertrophic obstructive cardiomyopathy

Abstract: Background: Nonsustained ventricular tachycardia (NSVT) is an independent risk factor for sudden cardiac death (SCD) in patients with hypertrophic obstructive cardiomyopathy (HOCM). However, data concerning the correlations of cardiac biomarkers and NSVT in HOCM are rather limited. Hypothesis: Our study aimed to investigate the associations between the occurrence of NSVT and circulating biomarkers representing myocardial injury (cardiac troponin I, cTnI), cardiac function (N-terminal pro-brain natriuretic pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…We found that patients with elevated levels of cTnI and CK-MB had more severe clinical phenotypes, consistent with previous reports. [8][9][10][11][12] The elevated levels of cTnI and CK-MB were associated with greater LV wall thickness, presumably because thicker myocardium causes more severe intimal hyperplasia and luminal reduction within coronary arteries, triggering microvascular dysfunction. 22,23 Consequently, the coronary arterial supply is insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that patients with elevated levels of cTnI and CK-MB had more severe clinical phenotypes, consistent with previous reports. [8][9][10][11][12] The elevated levels of cTnI and CK-MB were associated with greater LV wall thickness, presumably because thicker myocardium causes more severe intimal hyperplasia and luminal reduction within coronary arteries, triggering microvascular dysfunction. 22,23 Consequently, the coronary arterial supply is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The results of small-scale studies have suggested associations between troponins/CK-MB and the extents of hypertrophy, 8 myocardial strain, 9,10 cardiac fibrosis, 11 arrhythmia, 12 and mortality 13 among patients with HCM. However, the existing evidence is insufficient to warrant the inclusion of troponins and CK-MB in the risk stratification strategies for HCM.…”
mentioning
confidence: 99%
“…Furthermore, several studies have investigated the prognostic role of cTNI with regard to the occurrence of ventricular tachyarrhythmias. For instance, Liu et al found that elevated cTNI levels were associated with the occurrence of nonsustained VT in 755 patients with hypertrophic obstructive cardiomyopathy [ 36 ]. However, cTNI did not affect the risk of the composite arrhythmic endpoint (i.e., recurrent ventricular tachyarrhythmias, appropriate ICD therapies and SCD) at long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…CTnI is an important index to evaluate the therapeutic effect and prognosis of patients with heart disease. 15 Therefore, in patients with acute heart failure complicated with respiratory failure, monitoring of NT-pro BNP and cTnI levels in addition to blood gas analysis indexes may help in inhibiting the progress and aggravation of heart failure. Our study showed that the expression of NT-pro BNP and cTnI in the NIV group was lower than that in the control group, which was consistent with the results of Westhoff M and De Palo M. 16,17 Noninvasive ventilator-assisted ventilation technology is easy and safe.…”
Section: Discussionmentioning
confidence: 99%